MECHANISMS FOR IMPROVING THE QUALITY AND EFFICIENCY OF EDUCATION IN THE PROCESS OF IMPLEMENTING ADVANCED FOREIGN EXPERIENCES (Universal International Scientific Journal, 2026)
This article analyzes the mechanisms for improving the quality and efficiency of education by introducing advanced foreign experiences in the education system from a scientific, theoretical and practical perspective. In particular, the results of the Programme for International Student Assessment PISA conducted by the OECD, the Trends in International Mathematics and Science Study TIMSS organized by the International Association for the Evaluation of Educational Achievement IEA, as well as the advanced approaches of the education systems of Finland, Singapore, South Korea and Germany, highlight effective mechanisms. The main areas of the study are digital educational technologies, a competency-based approach, improving the assessment system, improving the skills of teaching staff and modernizing educational management.
Keywords: : quality of education, efficiency, advanced foreign experience, PISA, TIMSS, competency-based approach, digital technologies, education reform.